Enhanced Drag Reduction Performance of Nanocomposites: The Effects of Surface Modification of Nano Silica. Issue 4 (July 2017) - Dai, Xiaodong; Zhang, Guicai; Li, Bing; Ge, Jijiang; Wang, Xuewu; Yin, Shuming
In this paper, nanocomposite was synthesized with nano silica and poly-α-olefin, and the effects of surface modification to the nano silica on its drag reduction performance were investigated. The dosage coupling agent, Y-aminopropyltriethoxysilane, and the modification temperature were studied intensively through surface hydroxyl and oil adsorption analysis. The test results indicated that the hydroxyl number of the silica was decreased by Y-aminopropyltriethoxysilane modification, with improved lipophilicity and oil adsorption. At 50°C, the optimum Y-aminopropyltriethoxysilane dosages were 15% for Nano-Si-10, 5% for Nano-Si-20, and 10% for Degussa-R972. The modification significantly changed the nano silica surface properties and enhanced the interaction with poly-α-olefin. Through drag reduction and shear resistance tests by rotating disk 40 mins degradation and testing loop 2 times shearing, it was shown that the nanocomposite possessed good drag reduction and excellent shear resistance properties.